1988
DOI: 10.1524/ract.1988.43.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Muonium Hot Atom Chemistry in Gases

Abstract: The experimental determination of muonium hot atom (Mu*) yields in gases is discussed, with reference to earlier work in the alkanes as well as new data in H 2 , D,. It is concluded that inelastic scattering dominates the energy loss process. In comparison with corresponding results for hot tritium, Mu* is found to be considerably less reactive. Although quantitative interpretation of this difference is not yet available, it is likely that muonium is a more sensitive probe of the topography of the underlying p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Past #tSR studies22,23,41 have shown that PL in low-pressure gases is due to cyclic charge exchange at epithermal energies, affecting both PMu and PD. Thus, one can define the (relative) amount of muonium or diamagnetic muon,/, in terms of their polarizations, as /d = 1 "/mu = p Plp (6) "Mu t "D which is plotted in Figure 4 for CH4 and Figure 5 for C3H8. It is less clear how to properly account for PL at higher densities where the period of charge exchange cycles becomes much less than the period of the hyperfine oscillation, so that there is no associated depolarization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past #tSR studies22,23,41 have shown that PL in low-pressure gases is due to cyclic charge exchange at epithermal energies, affecting both PMu and PD. Thus, one can define the (relative) amount of muonium or diamagnetic muon,/, in terms of their polarizations, as /d = 1 "/mu = p Plp (6) "Mu t "D which is plotted in Figure 4 for CH4 and Figure 5 for C3H8. It is less clear how to properly account for PL at higher densities where the period of charge exchange cycles becomes much less than the period of the hyperfine oscillation, so that there is no associated depolarization.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, inefficient moderation and large reactive cross sections are requirements for large yields. To date, energy moderation in Mu* reactivity has been interpreted as being primarily due to inelastic scattering, 3,4,6 consistent with other studies of epithermal ( *, T*) reactivity 21,54,55 From studies of µ+ charge exchange,4,22,23,56 we expect the energy regime for Mu* reactivity to lie in the interval Et = 1 eV to E2 = £min s= 10-20 eV. While the values for £mi" for T* and H* are probably larger, the cross sections for both abstraction and substitution in the alkanes fall essentially to zero for kinetic energies much above 20 eV, with that for substitution being more sharply peaked, and with threshold energies of near 0.5 eV and 1.5 eV, respectively.31,51,57 Thus it is reasonable to expect much the same energy interval for all H*-atom isotopes, with mass effects becoming important only in the cross sections and kinematic factor a(M, E) of eq 10.…”
Section: Discussionmentioning
confidence: 99%